Meat yield characteristics of broiler fed different levels of palm oil - Das, GB; Hossain, ME; Islam, MM; Akbar, MA (Bangladesh Journal of Animal Science, 2014)
Seven hundred fifty day old unsexed broiler chicks were used in a 35-d trial to examine the effect of supplementing different levels of palm oil on lean meat yield of broilers. The chicks were randomly distributed following a completely randomized design in five treatment groups having three replications per treatment. Each treatment had 150 birds with 50 birds per replicate. Five diets were formulated using locally available ingredients as diet without oil, diet containing 2.0%, 3.0%, 4.0% and 5% palm oil. Results indicated that weight gain of broilers differed significantly (p<0.05) among the treatment groups at 2nd wk. The weight gain of 4% palm oil group was higher (p<0.05) than 5% dietary oil group at 2nd wk. At 5th wk, weight gain of without oil and 5% oil groups were similar (p>0.05). Feed intake significantly (p<0.05) differed at 2nd wk. Broiler that received 5% dietary palm oil group consumed the least amount of feed compared to others. No significant differences were found among the treatments in whole experimental period for feed conversion ratio. The meat yield characteristics did not differ (p>0.05) among the broilers receiving different levels of palm oil in diets except gizzard, wing meat and dark meat. Supplementation of oil resulted in significantly (p<0.05) increased dark meat weight at 3% level. Dressed yield of broilers had an increasing trend at increased level of palm oil supplementation up to 4%. However, at 5% supplementation dressed yield was lowest. Similar results were also observed in breast meat. Thigh meat was progressively increased for supplementation of oil up to 3% level, at higher level it tended to decrease. DOI: http://dx.doi.org/10.3329/bjas.v43i2.20705 Bang. J. Anim. Sci. 2014. 43 (2): 112-117